Clinical and virological implications of A1846T and C1913A/G mutations of hepatitis B virus genome in severe liver diseases. (4th March 2018) - Zang, Hong; Xu, Zhihui; Liu, Yan; Li, Xiaodong; Rong, Yihui; Jiang, Ling; You, Shaoli; Hu, Jinhua; Zhao, Jun; Xu, Dongping; Xin, Shaojie
Abstract: Objective: Mutations occurring within different genes of hepatitis B virus (HBV) genome may have different clinical implications. This study aimed to observe the clinical and virological implications of the A1846T and C1913A/G mutations of HBV genome in the development and treatment outcome of severe liver diseases, which has not been previously determined. Materials and methods: A total of 438 cases of patients with liver diseases were retrospectively reviewed, including 146 with mild chronic hepatitis B infection (CHB-M), 146 with severe chronic hepatitis B infection (CHB-S), and 146 with acute-on-chronic liver failure (ACLF). Partial or full-length HBV genome was directly sequenced. Replicons containing A1846T, C1913A or other mutant sequences, or the wild-type counterparts were constructed respectively, and then transfected into HepG2 cells for phenotype analysis. Results: There was significant difference in the detection rates of A1846T (30.82%, 40.41% and 55.48%, respectively) and C1913A/G (15.52%, 28.77%, and 35.62%, respectively) among patients with CHB-M, those with CHB-S, and those with ACLF ( p < .01). A1846T was significantly associated with the mortality of ACLF patients within six months after the disease onset (OR 1.704, p = .041). In vitro experiment revealed that A1846T mutant resulted in 3.20-fold and 1.85-fold increase of replication capacity and promoter activity, respectively compared with wild type counterpart ( p < .001), while C1913A led to a significant decrease of core protein expression ( p < .05). Conclusion: Occurrence of A1846T and C1913A is positively associated with clinical presentations of severe liver disease. A1846T mutation is significantly associated with poor prognosis of ACLF.